Green Intellectual Capital, Enterprise Risk Management and Corporate Social Responsibility on Environmental Performance and Financial Performance - Suhardjo Suhardjo; Khomsiyah Khomsiyah (Institut Bisnis dan Teknologi Pelita Indonesia, 2025)
The purpose of this study is to obtain an overview of green intellectual capital (GIC), corporate risk management (ERM), corporate social responsibility (CSR), company size (SIZ), company age (AGE) and company certification (CER) in influencing environmental performance and financial performance. Helping to describe the development of green-based human resources, resilient and adaptive risk management, and the role of implementing local wisdom-based corporate social responsibility in impacting the company's environmental and financial performance in the long term. The research method uses multiple linear regression analysis using SMART PLS version 4 on 105 primary consumer goods sub-sector companies (non-cyclical consumers) listed on the IDX for the 2016-2022 period. The results of the study concluded that hypothesis 1, hypothesis 4, hypothesis 5, and hypothesis 7 were accepted, while hypothesis 2, hypothesis 3, and hypothesis 6 were rejected. The recommendation of this study is that the company's green intellectual capital has a strong impact on environmental and financial performance. Corporate risk management has a strong impact on financial performance only. And corporate social responsibility has a negative impact on environmental performance and financial performance. While environmental performance has a strong impact on financial performance. Green intellectual capital and corporate risk management are important elements in enhancing a company's competitiveness, uniqueness and sustainability.